Peningkatan Kemampuan Literasi Dan Numerasi Pada Anak Usia 7-8 Tahun Melalui Kampus Mengajar - Hasnah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The teaching campus is a program from the Ministry of Education, Culture, Research and Technology which provides students with the opportunity to study outside campus forone semester. Through the Teaching Campus program, students have activities that are their responsibility to help with learning activities at school. In this program, students partner with teachers at SDN 063 Sarolangun Hamlet, Sarolangun District, Sarolangun Regency, Jambi Province. The main task of this campus teaching program is to assist teachers in implementing learning in schools, especially to improve literacy and numeracy, increase student creativity and help students adaptto technology.The Teaching Campus Program by sending students as school change partners has helped implement teaching and learning activities.